Busy Book Media Development In Introducing Early Children's Lampung Language at Tk Bina Pertiwi Katon State Pesawaran - Sri Primartin; Leli Fertiliana Dea; Muhammad Yusuf (Journal of Childhood Development, 2021)
Knowing the local language has been introduced from an early age so that children do not forget their respective regional languages, including the regional language of Lampung. Introducing the Lampung language starting from counting in the Lampung language, singing, and mentioning the simple vocabulary of the Lampung language. The aim of this research is to develop the Busy Book media as a learning medium to introduce the Lampung language for early childhood, see the feasibility of the Busy Book as a learning medium to introduce the Lampung language in child. Research in the form of R & D taken from the development of Brog and Gell, the subject of this research is TK Bina Pertiwi Desa Pejambon, Negeri Katon District, Pesawaran Regency with a questionnaire-based research instrument that is validated by material experts and media experts, and teachers at Bina Pertiwi Kindergarten, Pejambon Village, Negeri District. In Katon Pesawaran District, the type of data produced is qualitative data which is analyzed with new criteria of assessment to determine the quality of the Busy Book being developed. The result of this research is that the Busy Book media as a learning medium for early childhood in Bina Pertiwi Kindergarten is very feasible to use and can also improve Lampung language skills in early childhood.